Periodic and uniform nanogratings formed on cemented carbide by femtosecond laser scanning - Lian, Yunsong; Deng, Jianxin; Xing, Youqiang; Lei, Shuting; Yu, Xiaoming (My University, 2013)
Periodic and uniform nanogratings are fabricated by femtosecond laser scanning on cemented carbide. Specifically, three experiments are designed to study the influence of single pulse energy, scanning speed, and scanning spacing on the period and the uniformity of the formed nanogratings. The results show that the sample with single pulse energy of 2 μJ, scanning speed of 1000 μm/s, and scanning spacing of 5 μm shows the best quality of nanogratings among all the tested samples at different processing parameters. The uniformity of the nanogratings is largely determined by single pulse energy, scanning speed, and scanning spacing. Single pulse energy and scanning speed significantly affect the period of the nanogratings, whereas the period of the nanogratings maintains a fixed value under different scanning spacings. The period of the nanogratings increases gradually with the decrease of the single pulse energy and the increase of the scanning speed, respectively.
Keywords: Femtosecond laser; Uniform nanogratings; Nanograting period; Cemented carbide